(untitled) (Eurasian Journal of Ecology, 2016)
Researches on receiving of biogas with using of city tree waste phytomass was carried out. Microbiocenoses of methanogenesis process was studied. It was shown, that the greatest exit of methane was observed at using of crushed biomass of high water plants and the adapted association of methanogens. It was established, that the mix of city tree waste with active sludge and drains of clearing stations was more perspective for application.